2009
DOI: 10.1021/ef801047f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Polycyclic Aromatic Hydrocarbon Indicator for the Onset of Coke Formation during Visbreaking of a Vacuum Residue

Abstract: To identify hydrocarbons that might be sensitive indicators of coke formation in visbreaking, experiments have been conducted on a vacuum residue at 410 °C with residence times of up to 60 min in a microreactor. An induction period of 40 min prior to coke formation was observed, consistent with previous laboratory studies, with the changes in bulk aromaticity being small. As an example of trace aliphatic components, the distribution of hopanes proved to be highly sensitive to cracking severity but not to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…However, an aromatic product with elemental formula similar to that of anthracene whose yield tends to increase during visbreaking was generated at 410 °C. 29 The data indicate that the RSM bio-crude is similar to decant oil (C 100 H 110 ON) 32 while the WSG bio-crude are more similar to those of conventional petroleum. Therefore, 410 °C seems to be a critical temperature for the breakage of C-H bonds and generation of H 2 O and light hydrocarbons in the gas phase, while lower temperature should be used to promote the C-O bond breakage but retain hydrogen into the bio-crude.…”
Section: Thermo-t Conversionsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, an aromatic product with elemental formula similar to that of anthracene whose yield tends to increase during visbreaking was generated at 410 °C. 29 The data indicate that the RSM bio-crude is similar to decant oil (C 100 H 110 ON) 32 while the WSG bio-crude are more similar to those of conventional petroleum. Therefore, 410 °C seems to be a critical temperature for the breakage of C-H bonds and generation of H 2 O and light hydrocarbons in the gas phase, while lower temperature should be used to promote the C-O bond breakage but retain hydrogen into the bio-crude.…”
Section: Thermo-t Conversionsmentioning
confidence: 94%
“…These data are in agreement with the findings of Ogbuneke et al that showed a reduction in coke formation during visbreaking of heavy vacuum residues with addition of more than 2 wt% water probably due to gasification reactions. 26 3.3 Bio-crude characterisation 3.3.1 Elemental analysis and calorific values. Table 3 shows the elemental analysis of the bio-crudes from Thermo-t.…”
Section: Thermo-t Conversionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coking tendencies of various vacuum residues during visbreaking, which depend on the time and temperature of exposure, have been the subject of several studies. , An increase in the harshness of the visbreaking conditions speeds up the conversion. It leads to the formation of carbon structures without hydrogen, which enter into condensation and polymerization reactions generating insoluble polycondensed structures, ultimately leading to coke formation.…”
Section: Introductionmentioning
confidence: 99%